2015
DOI: 10.1002/ca.22654
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the oral and craniofacial manifestations of cri du chat syndrome

Abstract: Cri du chat syndrome is an autosomal disorder. Because it affects few people in the population it is considered a rare disease, yet it is one of the most common autosomal chromosomal syndromes in humans. It entails pathognomonic alterations that affect the craniofacial and oral anatomy of patients. The aim of this study is to review these craniofacial and oral abnormalities in patients with Cri du chat syndrome. The PubMed Medline database was searched using two different strategies. First, we used “Dentistry”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
6
0
4
Order By: Relevance
“…Moreover, Rodríquez-Caballero et al (31) observed some dental defects with a lower percentage, like dental opacities (33%), dental agenesis (9%), macrodontia (6%), supernumerary teeth (3%), root resorption (3%) and dental transposition (3%). A comprehensive review centered in oral and craniofacial manifestations of this syndrome has recently been published by the authors of this review (34). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Rodríquez-Caballero et al (31) observed some dental defects with a lower percentage, like dental opacities (33%), dental agenesis (9%), macrodontia (6%), supernumerary teeth (3%), root resorption (3%) and dental transposition (3%). A comprehensive review centered in oral and craniofacial manifestations of this syndrome has recently been published by the authors of this review (34). …”
Section: Resultsmentioning
confidence: 99%
“…A large number of DS patients have lost teeth through aggressive periodontitis; could it be possible that some similar destructive process of the peri-implant support is taking place? Certain syndromes related to implant failure or with specific microbiological characteristics have been described [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in four out of the six DS evaluated patients, we found a reduction of the labial philtrum width. Alterations of this feature are often associated with syndromic condition [28,34]. In conclusion, despite the reduced patients number, this preliminary report allowed the identification of dysmorphic facial traits in the faces of adults affected by DS.…”
Section: Discussionmentioning
confidence: 78%